Pengaruh Persepsi Kemudahan, Persepsi Manfaat, Persepsi Harga dan Pemasaran Internet Terhadap Pemesanan Ulang Online Hotel di Bali - Pramudana, Komang Agus Satria; Santika, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
This research is conducted against a background of low online repurchase intention on the same online site, which is often found in online shopping, making online companies difficult to realize long-term and sustainable profitability. This study aims to determine the influence of perceived ease of use, perceived usefulness, perception of price, and internet marketing on online re-booking hotels in Bali. This research is done by quantitative approach, both descriptive and associative. Sampling method in this research is non probability sampling with purposive sampling technique. Data were collected from 120 respondents i.e. e-commerce users for online booking of hotel rooms in Bali. The results showed that perceived ease of use have a positive and significant effect on online re- booking; perceived usefulness have a positive and significant impact on online re-booking; price perceptions have a positive and significant impact on online re-booking; and internet marketing have a positive and significant impact on online re-booking.